Lecture notes. - Clarke, Ray (Raymond) (Wiley-Blackwell, 2014)
"In Diseases of the Ear, Nose and Throat Lecture Notes, 11th edition you will find everything on the topic that could crop up in a clinic or teaching session. This little gem of a book is clearly laid out with colour photographs and illustrations, is broken down into intuitive chapters and sections, and contains treatment boxes, all of which help those key concepts stick"--Provided by publisher.